Strain-controlled Graphene-Polymer Angular Actuator. (2019) - Gilbert, S. Matt; Molnar, Adam; Horton-Bailey, Donez; Yao, Helen Y.; Zettl, Alex
ABSTRACT: We demonstrate a suspended graphene-(poly(methyl methacrylate) (PMMA) polymer angular displacement actuator enabled by variable elastic modulus of the perforated stacked structure. Azimuthal flexures support a central disc-shaped membrane, and compression of the membrane can be used to control the rotation of the entire structure. Irradiating the PMMA on graphene stack with 5 kV electrons in a convention scanning electron microscope reduces the elastic modulus of the PMMA and allows graphene's built in strain to dominate and compress the flexures, thus rotating the actuator.